2017
DOI: 10.1016/j.jand.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in Infancy Is Associated with Body Mass Index in Adolescence: A Retrospective Cohort Study Comparing American Indians/Alaska Natives and Non-Hispanic Whites

Abstract: Background American Indians and Alaska Natives (AI/ANs) have the highest obesity prevalence in the United States, but the influence of early childhood variables on body mass index (BMI) is not well understood. Previous studies have investigated the association between breastfeeding in infancy and offspring BMI, but rarely included AI/ANs. Objective This study investigated the association between breastfeeding in infancy and BMI in AI/AN and non-Hispanic White (NHW) adolescents and young adults. Design Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Although a prevalent mode of infant feeding, consumption of formula contributes to acute and chronic illnesses not limited to gastrointestinal infection, asthma, childhood obesity, and diabetes mellitus type II (American Academy of Pediatrics (2012); US Department of Health and Human Services (HHS), 2011). Methods to increase the likelihood for breastfeeding in American Indian (AI) communities are needed as breastfeeding may be a key component to reducing high obesity rates (Zamora-Kapoor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although a prevalent mode of infant feeding, consumption of formula contributes to acute and chronic illnesses not limited to gastrointestinal infection, asthma, childhood obesity, and diabetes mellitus type II (American Academy of Pediatrics (2012); US Department of Health and Human Services (HHS), 2011). Methods to increase the likelihood for breastfeeding in American Indian (AI) communities are needed as breastfeeding may be a key component to reducing high obesity rates (Zamora-Kapoor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a retrospective cohort study, a lower BMI was reported among AI/AN adolescents breastfed for .6 months. 37 Breastfeeding promotion is needed in AI/AN tribal communities and would ideally be coordinated by tribal entities and would involve community members, elders, and health care providers, including paraprofessionals. 38,39…”
Section: Breastfeedingmentioning
confidence: 99%